A aritmética de Lourenço Filho: um estudo sobre as dinâmicas de transformações do saber escolar em face de uma nova pedagogia - Soares, Marcia Guedes [UNIFESP] (2014)
This study aimed to analyze the Lourenço Filho’s arithmetic read in Aprenda por si!, A graduaded series of arithmetic’s exercises. It’s a textbook produced by the Biblioteca de Educação of the Companhia Melhoramentos, published between 1941 and 1953. Lourenço Filho has experience with the pedagogie as teaching as an art and as an active school. We investigate the transformations of arithmetic for primary school in research of historic character, based in documentary sources, having Roger Chartier as the main reference. The results showed the author’s appropriation practice that evidence a process of hybridization of the relationships that constitute him.